AB0-incompatibility of mother and fetus: the role of anti-glycan alloantibodies in the hemolytic disease of newborns - P. S. Obukhova (SPb RAACI, 2021)
The mother and fetus incompatibility due to Rh-factor, blood group or other blood factors can lead to hemolytic disease of the fetus and newborn (HDN). HDN is a clinical disease condition of the fetus and newborn as a result of hemolysis, when maternal IgG alloantibodies cross the placenta and destroy the red blood cells of the fetus and newborn. The child disease begins in utero and can dramatically increase immediately after birth. As a result, hyperbilirubinemia and anemia develop, that can lead to abortions, serious complications, or death of the neonates in the absence of proper therapy. The range of HDN has changed significantly now compared to previous decades. Half a century ago, HDN was considered an almost complete synonym of RhD-alloimmunization, and this was a frequent problem for newborns. By now due to the high effective of Rh-conflict prevention, immunological AB0-conflicts have become the most common cause of HDN. The review aimes to one of the main causes of jaundice and anemia in neonates at present, i.e. HDN due to immunological AB0-conflict of mother and newborn (AB0-HDN). The main participants of the AВ0- incompatibility mother and child are considered, namely A- and B-glycans, as well as the corresponding anti-glycan alloantibodies. Close attention is paid to the structure features of glycan alloantigens on the red blood cells of the fetus and adult. The possible correlation of the frequency and severity of HDN with the blood group of mother and child, as well as with the titer of maternal alloantibodies, has been considered. The influence of immunoglobulin G subclasses on the AB0-HDN development has been evaluated. In most cases, AB0-HDN appear when the mother has the blood group 0, and the fetus has the group A (subgroup A1) or the group B. Other rare incidences of AB0-incompatibility with severe course are occurred. As a whole the etiology of AB0-HDN is complex and the HDN severity is influenced by many factors. The authors have analyzed statistical data, as well as the prevalence of AB0-incompatibility and AB0-HDN in various regions of the world. Current approaches to the diagnosis of AB0-HDN are discussed in addition. By now the problems of AB0- HDN occurrence and developing of ways to overcome this disease remain relevant.